PENGARUH PENINGKATAN TRAFIK TERHADAP QUALITY OF SERVICE PADA LAYANAN INTERNET, IPTV, DAN VOIP DI JARINGAN FIBER TO THE HOME LABORATORIUM TELEKOMUNIKASI UNIVERSITAS BRAWIJAYA - Herfita, Najya Putri; Kusmaryanto, Sigit; Prijono, Wahju Adi (Jurnal Mahasiswa TEUB, 2024)
The use of digital internet-based services has become a primary need, especially in academic environments such as campuses.Triple Play services, which include internet, IPTV, and VoIP, are increasingly used to support daily activities such as teaching,research, and administration. However, an increase in the number of users or traffic can pose a problem that potentially disrupts service quality. Therefore, this study was conducted to understand how the increase in traffic affects Quality of Service (QoS).The research methodology includes predicting incoming traffic, which involves estimating the number of users, calculating trafficintensity, and determining traffic volume over a day. Network quality testing involves calculating the power link budget. Service quality testing includes measuring throughput, packet loss, delay, and jitter using Ettercap and Wireshark software.The results of the study show that the daily traffic volume is 669,600 Mbit for internet services, 201,600 Mbit for IPTV services, and 787.2 Mbit for VoIP services. The traffic intensity over a day is 18.6 Mbps for internet services, 5.6 Mbps for IPTV, and 0.262 Mbps for VoIP, with peak traffic activity occurring at 12:00 PM, 1:00 PM, and 2:00 PM. The calculated attenuation of 21.65 dB and receiver power of - 17.66 dBm indicate that the network can provide good service quality. An increase in traffic will lead to higher throughput, no packet loss, and a reduction in delay and jitter. High traffic can cause strain on the network capacity, particularly if the capacity is insufficient to handle the volume of traffic. Insufficient network capacity will result in decreased service quality, characterized by reduced throughput and increased packet loss, delay, and jitter. In such conditions, the services that experience significant quality degradation are VoIP and IPTV. Keywords: FTTH, Triple Play, Network Traffic, Quality of Service, Network Quality.